Heterojunctions of rGO/metal oxide nanocomposites as promising gas-sensing materials—A review - Abdullah, Norli; Norizan, Mohd Nurazzi; Abdul Halim, Norhana; Ngah Demon, Siti Zulaikha; Mohamad, Imran Syakir (MDPI, 2022)
Monitoring environmental hazards and pollution control is vital for the detection of harmful toxic gases from industrial activities and natural processes in the environment, such as nitrogen dioxide (NO2), ammonia (NH3), hydrogen (H2), hydrogen sulfide (H2S), carbon dioxide (CO2), and sulfur dioxide (SO2). This is to ensure the preservation of public health and promote workplace safety. Graphene and its derivatives, especially reduced graphene oxide (rGO), have been designated as ideal materials in gas-sensing devices as their electronic properties highly influence the potential to adsorb specified toxic gas molecules. Despite its exceptional sensitivity at low gas concentrations, the sensor selectivity of pristine graphene is relatively weak, which limits its utility in many practical gas sensor applications. In view of this, the hybridization technique through heterojunction configurations of rGO with metal oxides has been explored, which showed promising improvement and a synergistic effect on the gas-sensing capacity, particularly at room temperature sensitivity and selectivity, even at low concentrations of the target gas. The unique features of graphene as a preferential gas sensor material are first highlighted, followed by a brief discussion on the basic working mechanism, fabrication, and performance of hybridized rGO/metal oxide-based gas sensors for various toxic gases, including NO2, NH3, H2, H2S, CO2, and SO2. The challenges and prospects of the graphene/metal oxide-based based gas sensors are presented at the end of the review.